Interview with María Galindo - Sánchez Miranda, Bertha (Filanderas, 2022)
María Galindo is founder of the Bolivian Movimiento de Mujeres Creando and perhaps one of the most radical feminists in Latin America. For nearly two decades she has been decades travelling to Spain to present some of her work. A few months ago she was in Zaragoza presenting her new book Feminismo Bastardo. The presentation of the book took place at the Centro Luis Buñuel Social Centre, attended by more than a hundred people. After the presentation of the book, a group of migrant feminist women met with her. Most of them came from Latin America from Latin America and the Sahara, with different migratory situations, ranging from naturalised women who arrived decades agoto political asylum seekers who have been in these lands few winters in these lands. This multi-voice interview gathers part of this intimate conversation between María Galindo and the group of migrants, and the reflections that shook the Luis Buñuel.
Keywords: María Galindo; Feminism; Bolivia; Latin American